Effect of Urbanization on Water Quality And Discharge in Taman Mayang, Selangor - Md. Ali, Zarina (2000)
Urbanization in Malaysia has taken place very rapidly in the last ten years or more due to the economic boom in the country especially in the Klang Valley. One direct consequence of rapid urbanization is the rapid increase in impervious areas such as roads and highways, pavement and parking lots. Industrial, commercial and domestics activities resulting in severe pollution and flood problems in urban areas. The main objective of this study is to determine the effect of urbanization on water quality and discharge in urban area. The Taman Mayang catchment area was selected as a case study. Water quality analysis was done on the water with in-situ measurements and laboratory analysis. The parameters are pH, Temperature (Temp), Turbidity, Electric Conductivity (EC), Dissolved 'Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (AN), Suspended Solid (SS), Sulphate (S04), Chromium (Cr), Boron (B), Sulphide (S2), Copper (Cu), Iron (Fe), Chlorine (Cl), Cyanide (Cn), Nickel (Ni), Phosphate (P04), Mercury (Hg), Cadmium (Cd), Arsenic (As), Manganese (Mn), Zinc (Zn), Plumbum (Pb), Stanum (Sn) and Phenol. Two methods were used to estimate Water Quality Index (WQI), which were Harkins' WQI and DOE-WQI. Based on results for this study, the water quality of the river in Taman Mayang can be classified into Class III and IV by on overall river classification based on Harkins' WQI and DOE-WQI. The study showed that the Taman Mayang discharge was polluted and needs intensive treatment to clean the river. For an urban area, Taman Mayang has BOD value ranging between 3.5 - 7.0 mg/l and COD value which ranges from 20.0- 49.0 mg/l. The pollution sources were identified to originate from the industrial and residential areas. The other parameters did not have serious effect to the environment and human population. From the hydrologic study, rainfall intensity was found to be 86.36 mm/hr for 2 year return period, 134.62 mm/hr for 10 year return period and 187.96 mm/hr for 100 year return period. The total discharge from Taman Mayang were 20.51 m3/s for 2 year return period, 31.87 m3/s for 10 year return period and 44.64 m3/s for 100 year return period. The results of this study can be used as a basis for future studies on water quality on the similar urbanized areas in Malaysia.